Teacher-parent collaboration for developing student character in online learning - Rahmat Aziz; Meinarni Susilowati; Masturin Masturin; Zaenuddin Hudi Prasojo (International Journal of Evaluation and Research in Education (IJERE), 2023)
Teachers, parents, and students have had difficulty with character development exercises in online learning programs. Students’ character quality has suffered as a result of these issues. This study described the essence of reading fondness, learning discipline, and social care in developing the students’ character development. In addition, this study also aimed to analyze the role of teachers and parents in character development during the online learning process. Students, teachers, and parents provided information via online questionnaires and interviews. Descriptive quantitative analysis, thematic analysis, and reflective thinking were used to analyze the data. The findings revealed that teachers and parents faced challenges that impacted student character quality. Teachers and parents have limited opportunities to shape a students’ character. Instead, they must collaborate to develop it. The limitation of this study lies in the online data collection process, thus suggesting the need to use a more in-depth method to gain a more comprehensive understanding of the case.